Comparison of Health Care Performance in Counties - Molienė, Ona; Žemgulienė, Jolanta (Ekonomika, 2002)
The basic focus of the article is introduction of health development index as the tool for the comparative analysis of health care system performance in counties. The method for the health development index calculation is based on modelling of the appropriate system of health care indicators, standardisation of the quantitative indicators, calculation of health development indicator as the average of standardised indicator values. The proposed system of health care indicators includes indicators of following groups: health care resources and activity, mortality, morbidity, emergency care activity, demography. Factor analysis is used for the grouping of indicators. Selected factors account for the 74 per cent of total variance.